IMPLEMENTATION OF RESTORATIVE JUSTICE IN INDONESIAN GENERAL COURTS(BASED ON THE DECREE OF THE DIRECTOR- GENERAL OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA No. 1691/DJU/SK/PS.00/12/2020) - Sinaga, Haposan Sahala Raja (International Journal of Research -GRANTHAALAYAH, 2021)
The shift in punishment in the criminal justice system prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punish- ments such as social work and others carried out with a restorative justice approach. Focusing on the process of direct criminal responsibility from the perpetrator to the victim and society, if the perpetrator and victim and the community whose rights have been violated feel that justice has been achieved through collective deliberation efforts, punishment can be avoided. The perpetrator is not the main object of the restorative justice approach, but the sense of justice and conflict recovery itself are the main objects. The Supreme Court of the Republic of Indonesia, on December 22 2020, through the Director-General of the General Courts Agency, has made Decree Number: 1691/DJU/SK/PS.00/12/2020 concerning the Enforcement of Guidelines for the Implementation of Restorative Justice in the Indonesian General Courts. With the normative juridical research method, with the nature of qualitative descriptive research, by examining secondary data obtained through the Decree of the Director-General of the General Courts of the Supreme Court of the Republic of Indonesia Number: 1691/DJU/SK/PS.00/12/2020 and other related regulations which has relevance to the implementation of restorative justice in the Indonesian general courts’ environment. The results of the research show the implementation of restorative justice in the Indonesian general courts, as stated in the Decree of the Director-General of the Supreme Courts Number: 1691/DJU/SK/PS.00/12/2020, which must apply and be applied by all district courts in Indonesia, especially in terms of case settlement in action. Minor offenses, child cases, women in conflict with the law and nar- cotics cases. The existence of alternative case resolution through restorative justice can realize the principles of fast, simple and low cost with balanced justice.